Approach to innovative activities by Lithuanian companies in the current conditions of development - Adekola, Abel; Korsakienė, Renata; Tvaronavičienė, Manuela (Technological and Economic Development of Economy, 2008)
The paper aims to reveal the approach of Lithuanian companies towards innovations. In order to take into account conditions, specific to the considered country an, overview of Lithuanian economy with a closer look at demographic and employment tendencies is presented; analysis of statistically estimated innovation performance and state innovation policy performed. Insight into factors driving innovations into Lithuanian business companies is being made through questioning the randomly chosen 1001 Lithuanian business companies. The performed survey allows us to disclose how companies react to factors fostering and restricting innovations, how they perceive role of state policy in the process of innovative activities. Obtained results provide us with empirical evidences how business companies react to specific economic conditions, and if there is a sufficient correspondence between educational system and supply of know‐how susceptible employees demanded by business companies.Lietuvos įmonių požiūris į inovacinę veiklą dabartinio vystymosi sąlygomisSantrauka. Straipsnio tikslas – atskleisti Lietuvos įmonių požiūrį į inovacinę veiklą. Siekiant atsižvelgti į specifines šalies sąlygas, pateikiama Lietuvos ekonomikos apžvalga, daugiau dėmesio teikiama emigracijos ir nedarbo tendencijoms, pateikiama statistinė inovacinės veiklos ir šalies inovacijų politikos apžvalga. Pagrindinius veiksnius, lemiančius inovacijų kūrimą Lietuvos verslo įmonėse, padeda atskleisti atsitiktinai pasirinktos 1001 įmonės apklausa. Ši apklausa parodo, kaip įmonės reaguoja į veiksnius, skatinančius ir ribojančius inovacijas, kaip vykstant inovacinės veiklos procesui įmonės vertina valstybės inovacijų politiką. Gauti rezultatai leidžia daryti išvadas apie įmonių reakciją į specifines ekonomines sąlygas bei kvalifikuotos darbo jėgos pasiūlos ir paklausos lygį.Reikšminiai žodžiai: inovacijos, verslo įmonės, Lietuvos ekonomika, valstybės politika.First published online: 21 Oct 2010